2011 International Conference on Devices and Communications (ICDeCom) 2011
DOI: 10.1109/icdecom.2011.5738472
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Worldwide Spectrum Occupancy Measurement Campaigns for Cognitive Radio

Abstract: Cognitive radio is the emerging technology which provide the innovative approach to improve the spectrum utilization and alleviate the spectrum scarcity. Evaluation of the spectrum occupancy is the step toward the future deployment of cognitive radio. Worldwide several spectrum occupancy measurement campaigns have been performed at different location in context of cognitive radio. We reviewed past measurement campaigns performed by different research groups and analysis of empirical results. We further provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 13 publications
0
55
0
Order By: Relevance
“…From the figure, it can be observed that sensing with (20) outperforms than sensing with (19) in the presence of noise correlation. 1 More exact relation models can be acquired through measurements on the CR equipment. Figure 2 shows the sensing performance versus correlation coefficient at SNR value of -6 dB and β = 1/6 and it can be noted that with increased amount of noise correlation, the sensing with (19) decreases drastically and sensing with (20) provides better performance up to a certain value of correlation.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the figure, it can be observed that sensing with (20) outperforms than sensing with (19) in the presence of noise correlation. 1 More exact relation models can be acquired through measurements on the CR equipment. Figure 2 shows the sensing performance versus correlation coefficient at SNR value of -6 dB and β = 1/6 and it can be noted that with increased amount of noise correlation, the sensing with (19) decreases drastically and sensing with (20) provides better performance up to a certain value of correlation.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…However, different spectrum occupancy measurement campaigns carried out at different parts of the world show that the average spectrum occupancy rate is very low [1] and it shows spatial as well as temporal variations. In this aspect, innovative techniques to exploit the opportunistic usage of underutilized spectrum are needed.…”
Section: Introductionmentioning
confidence: 99%
“…As shown through measurement campaigns, a large percentage of the available spectrum is under-utilized either temporally or spatially [2]. In this case, a primary system could share a frequency band with a secondary system which uses the resources opportunistically so that it does not degrade the primary QoS.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the unlicensed bands may get heavily congested. On the other hand, several studies and measurements conducted around the world have indicated that the licensed RFS bands can be underutilized [2].…”
Section: Introductionmentioning
confidence: 99%